Characterizing reform and change of teacher education in China in the new era - Yiming, Zhu; Ping, Fang Yan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2011)
Starting with a brief overview of the history of teacher education development in China, this paper aims to shed light on a few major positive characteristics in the reform and change of teacher education in China occurred in the past decade. These include changing role of the central government, innovations in curriculum and instruction in pre-service teacher education and strengthening of in-service teacher development. Challenges and issues faced by the reform and development of teacher education in China will be discussed in the final part of the paper together with a brief discussion on directions for the future.